Radical Prostatectomy: from Open Surgery towards Robotic Laparoscopy - W. F. Wieland; M. Burger; S. Denzinger; W. Otto; V. N. Pavlov (Креативная хирургия и онкология, 2020)
Radical prostatectomy was first performed more than 100 years ago and has since become the gold standard in treatment of localized prostate cancer. Open surgery has been almost entirely replaced by robotic operations referred to as robot-assisted radical prostatectomy (RARP). Th e article introduces the basics of this innovative standard of operative access and tackles medical and historical aspects, oncological, medical and economic management pros and contras of robotic aid over open radical prostatectomy. Surgical trauma in RARP is clearly less pronounced compared to open surgery due to a much earlier postoperative mobilisation and a faster rehabilitation of patients leading to a statistically significant reduction in the length of hospital stay after RARP. Along with advances in intracorporeal imaging with 16-fold optical magnification coupled with shorter urethral catheterisation, RARP facilitates an earlier start of pelvic floor exercises, which reduces postoperative incontinence and need for pain relievers. Th e already mentioned technical advantages of the robotic method hold value to both patient and surgeon by securing instant access for an experienced colleague without interrupting the surgery. Noteworthy, the increasing advancement of robotic systems across the globe is leading urologist surgeons to abandon open operations. A drawback of the robotic method is much higher economic costs. However, greater expenditures may pay off in the long run by shorter hospital stays, faster rehabilitation and fewer complications demanding extra management and care.